GENERALIZED ANALYSIS OF THE RESULTS OF GENETICALLY ENGINEERED BIOLOGICAL THERAPY: SEARCHES FOR NEW PATTERNS - Yakov Aleksandrovich Sigidin; G V Lukina (Научно-практическая ревматология)
The clinical analysis of the results of genetically engineered biological therapy identifies a number of patterns of the mechanism of action of this therapy and the pathogenetic features of rheumatic diseases. The results of using genetically engineered biological agents (GEBA) having different mechanisms of action allow one to identify categories of rheumatoid arthritis patients with different pathogenetic features. Various cytokines can play a major pathogenic role in a clinically similar inflammatory process. The therapeutic effect of tumor necrosis factor-α (TNF-α) inhibitors exhibits the predominance of their nonspecific anti-inflammatory activity over the immunosuppressive one. Contrary to the previous ideas of cytokine hierarchy, TNF-α neutralization does not block the effects of interleukin 6 (IL-6). Anti-B-cell therapy is most effective in patients with significant autoimmune disorders; a contrary pattern is observed when TNF-α inhibitors are used. TNF-α is very important in the development of an inflammatory process in ankylosing spondylitis (AS) while the role of IL6 is insignificant. Autoimmune disorders in AS are not marked; whereby predominantly immunotropic GEBAs (rituximab and abatacept) are ineffective in this disease. The blocking of a biological reaction to inflammation cannot coincide with the suppression of the inflammatory process proper.